Can multi‐species shark longline fisheries be managed sustainably using size limits? Theoretically, yes. Realistically, no. Issue 9 (15th July 2020) - Smart, Jonathan J.; White, William T.; Baje, Leontine; Chin, Andrew; D'Alberto, Brooke M.; Grant, Michael I.; Mukherji, Sushmita; Simpfendorfer, Colin A.
Abstract: Size limits are a common fisheries management strategy that are applied to many fisheries and species. Most size limits use a minimum legal size to protect adult fish as per the 'reproduce at least once' paradigm, where stock collapse becomes impossible if every adult can produce one spawner prior to harvest. These approaches can be useful in fisheries where determining catch is difficult and therefore catch limits can be ineffective and potentially cause stock decline. Shark longline fisheries can be complicated to manage due to a deficiency of species‐level reporting. Catch limits are therefore difficult to determine, creating a need for other management measures. Here, three different size‐based management approaches were tested using the shark longline fishery from Papua New Guinea as a case study. These approaches included minimum size, maximum size and harvest slot approaches. Age‐structured Leslie matrix models revealed a broad range of productivities for 12 commonly caught species, ranging from low population growth rates of 1% per year for pelagic thresher sharks Alopias pelagicus to >33% per year for blue sharks Prionace glauca . Therefore, different harvest strategies were required for each species to be fished sustainably. However, management could be applied by grouping similar and easily distinguishable groups of species together. Synthesis and applications . The most pragmatic harvest strategy for all shark species included in this study was to limit harvest to mature individuals using minimum legal sizes. This provided sufficient resilience for all species to tolerate higher levels of fishing mortality than the Papua New Guinea (PNG) longline fishery could impose. Legal minimum lengths were derived from the largest length‐at‐maturity within each species group. However, while this produced a sustainable harvest strategy, issues with selectivity, post‐release mortality, interactions with other fisheries, economic viability and illegal, underreported and unregulated fishing were challenges to restricting fishing to the correct size classes and overall management efficacy. Therefore, while theoretically viable harvest strategies were outlined, it is apparent that size limits would not ensure that these shark species are fished sustainably. Therefore, the PNG longline fishery cannot operate sustainably if it were to reopen using size limits as its sole management strategy. Abstract : The most pragmatic harvest strategy for all shark species included in this study was to limit harvest to mature individuals using minimum legal sizes. This provided sufficient resilience for all species to tolerate higher levels of fishing mortality than the Papua New Guinea (PNG) longline fishery could impose. Legal minimum lengths were derived from the largest length‐at‐maturity within each species group. However, while this produced a sustainable harvest strategy, issues with selectivity, post‐release mortality, interactions with other fisheries, economic viability and illegal, underreported and unregulated fishing were challenges to restricting fishing to the correct size classes and overall management efficacy. Therefore, while theoretically viable harvest strategies were outlined, it is apparent that size limits would not ensure that these shark species are fished sustainably. Therefore, the PNG longline fishery cannot operate sustainably if it were to reopen using size limits as its sole management strategy. Photo taken and provided by Shin Arunrugstichai. Translated Abstract ‐ Tok Pisin: Ol kain lo bilong lukautim pis we ol i save putim mak long hamas pis long kisim bai i hat long wokim taim yumi ino save gut long hamas pis tru yumi wok long kisim long fisaris. Olsem na wanpla wei long lukaitim pis em long mekim lo long kisim pis long rait sais. Taim yumi putim displa kain lo bai yumi givim taim long ol pis i ken kamap bikpla na kamapim ol liklik pis, olsem na taim yumi kisim ol bikpla pis, bai ol liklik pis i stap yet long solwara na pis bai ino pinis olgeta. Taim yumi ino save gut long wanem kain pis yumi wok lo kisim em bai hat lo putim ol lo long lukautim pis long fisaris. Displa em i save kamap long sak fisaris, igat kain kain sak tasol planti taim yumi ino save gut long wanem kain sak stret yumi wok long kisim. Olsem na putim lo long kisim sak inap long mak em bai hat na mipla mas painim narapla ol lo bilong lukautim ol sak bai ol ino ken pinis olgeta taim yumi kisim planti planti sak long fisaris. Long displa wok painim aut mipla lukluk long tripla rot bilong wokim ol lo bilong lukautim ol sak insait long sak fisaris long Papua New Guinea (PNG). Displa wok mipla i bin usim ol Age‐Structured Leslie matrix model na displa i bin soim olsem wanpla ten tu lo kain kain sak yumi save kisim long sak fisaries long PNG i gat ol kain kain wei long kamap long taim ol i stap liklik igo inap ol i kamap bikpa. Yumi ken lukim olsem ol thresher sak ( Alopia pelagicus ) em ol I save kamap isi isi na ol blue sak ( Prionance glauca ) em ol i kamap hariup moa. Olsem na wanpla wei em yumi ken bungim wantem ol sak i gat wankain wei long kamap ananit long wanpla lo taim yumi laik putim ol lo long lukautim sak long fisaris. Long displa wok mipla i painim olsem putim lo long kisim rait sais sak em wanpla wei long lukautim ol sak bai i no inap pinis long solwara taim yumi wok long kisim sak long fisaries. Tasol long wankain taim yet igat ol narapla samting olsem sak i save dai taim ol i hukim pinis na ol i laik putim bek long solwara, ol narapla fisaris tu i save hukim ol sak, ol kampani i ronim sak fisaris i mas wokim moni, na tu planti taim ol kampani ino save tok aut stret long wanem kain sak ol i save kisim, na ol i save burukim ol lo bilong lukautim pis long solwara. Em olsem na em bai hat long usim kain ol lo. Nau yet sak fisaris ino wok long kamap long PNG tasol sapos i bai kamap ken long behain taim bai i olrait moa sapos yumi painim narapla wei long lukautim ol sak. Sapos yumi behainim yet displa lo bilong kisim rait sais sak em bai ol sak i ken pinis olgeta long solwara.